Online Learning Materials: How Are They Being Used? - Cooper, Martin G.; Pagram, Jeremy E. (INTI University College, 2009)
Most universities are embracing Computer Managed Learning (CML) systems such as WebCT and & blackboard as their preferred mode of distance education and, in many cases, their preferred mode of distributing course materials to on campus students. Thus, paperless modes of document and content delivery such as Microsoft Word documents, podcasts, and video lectures are becoming the norm. The authors wondered how students made use of these materials, Are they being used in the ways that the providers imagined and are they the resources that the students want to use? This paper reports on a study that examined how and where some students at Edith Cowan University use the electronic documents distributed to them through the university CML system.